A nonfullerene acceptor with π-conjugation extended end groups to achieve enhanced photovoltaic performance. (9th March 2023) - Liu, Chunyan; Wu, Zhihui; Qiu, Nailiang; Li, Chenxi; Lu, Yan
Abstract : The π-conjugation extension on terminal unit enables high-efficiency photovoltaic performance, benefiting from the enhancement of J sc and FF. Abstract : An acceptor–donor–acceptor (A–D–A) type nonfullerene acceptor (NFA), namely TTNC, was designed and synthesized using a π-conjugation extension strategy on the terminal unit based on one successful NFA material TTIC. Benefiting from the end-extended conjugation, the new molecule shows red-shifted absorption, more ordered packing, and maintained energy levels compared with TTIC. These advantages contribute to achieving favorable phase separation morphology and strong light-harvesting ability for the donor/acceptor blend film. By combining with a wide band-gap polymer donor PBDB-T, the optimized TTNC based devices exhibit a high power conversion efficiency (PCE) of 11.34%, mainly originating from an enhanced short-current density ( J sc ) of 20.95 mA cm −2, especially an excellent fill factor (FF) of 71% which is obviously superior to that of TTIC (66%). The findings indicate that π-conjugation extension is an effective way to manipulate the absorption range, molecular packing and charge mobility of NFAs for an outstanding photovoltaic performance, which offers valuable insight for designing high-efficiency organic solar cells.